Predictors of Citation Rate in Psychology: Inconclusive Influence of Effect and Sample Size - Hanel, Paul H. P.; Haase, Jennifer (Frontiers in Psychology, 2017)
In the present article we investigate predictors of how often a scientific article is cited. In detail, we focus on the influence of two often neglected predictors of citation rate: effect size and sample size, using samples from two psychological topical areas. Both can be considered as indicators of the importance of an article and post-hoc (or observed) statistical power, and should, especially in applied fields, predict citation rates. In Study 1, both effect and sample size did not have an influence on citation rates across a topical area, both with and without controlling for numerous variables that have been previously linked to citation rates. In contrast, in Study 2 sample and partly effect sizes predicted citation rates, indicating that the relations vary even between scientific topical areas. The same applies to articles with statistically significant results that were found to be more often cited only in Study 2 but not in Study 1. It was also found that the journal impact factor is, on average, only a weak predictor of citation rate. The results indicate that the importance (or power) of scientific findings may not be as strongly related to citation rate as is generally assumed.